Patient Clinical Data Integration in Integrated Electronic Medical Record System using System Development Life Cycle (SDLC) - Rara Nur Salsabila; Yunita Wisda Tumarta Arif; Puguh Ika Listyorini; Ummi Athiyah (Proceeding of International Conference on Science, Health, And Technology, 2021)
Clinic is a health service facility that provides individual services, both providing basic and/or specialized medical services. The processing of medical record documents for outpatient services at the Al-Ikhlas Clinic, Sragen, is still carried out conventionally, starting from registration to storing documents. Often there is duplication, inaccuracy in recording, and presentation of reports that are not in accordance with the services at the service. The purpose of this study was to create medical records for inter-clinic patient data interventions with the development life cycle system development (SDLC) method so that it could provide benefits for officers in processing clinical patient data. This type of research is qualitative in nature using the SDLC system development method carried out by selecting projects, initiating and planning projects, analysis, design, Implementation, and maintenance. The subjects in this study were medical record officers and doctors, while the object under study included recording and processing patient medical record data. The development of the SDLC system is the main instrument to replace the old system as a whole or to improve the existing system, and the data sources used are primary data and secondary data. Electronic Medical Records built using the PHP programming language and MySQL database, where this system has the advantage of being able to speed up the registration process and data processing of computerized patient medical records as well as the ease of staff in making reports to clinic leaders. Electronic Medical Records of Al-Ikhlas Sragen Clinic can produce information in the form of patient data reports, diagnosis reports, action data reports, drug data reports, officer data reports, doctor data reports, polyclinic data reports, examination data reports, and patient registration data reports.